2004
DOI: 10.1179/027249304225013420
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity in neonates of mothers who have ingested aflatoxins

Abstract: This study was undertaken to assess whether aflatoxin M(1) concentrations in newborn infants correlated with those of their mothers and to determine whether the presence of aflatoxin M(1) in cord blood was associated with an increase in morbidity in the newborn. There was a strong correlation (r =0.797, p <0.0001) between mothers' and cord blood levels of aflatoxin. There was also a strong negative correlation between aflatoxin levels and birthweight (r =-0.565, p <0.001) but there was no association between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 34 publications
4
40
1
1
Order By: Relevance
“…Regarding the relation between aflatoxin B1 level in studied children and their mothers, a significant positive correlation was demonstrated between them which might be explained by exposure to maternal aflatoxin during fetal life as supported by the findings of Abdulrazzaq et al [22] who found a strong correlation (p <0.0001) between mothers' and cord blood levels of aflatoxin. Another possibility is that these children share the same type of foods with their mothers which might be the source of aflatoxin for both of them.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding the relation between aflatoxin B1 level in studied children and their mothers, a significant positive correlation was demonstrated between them which might be explained by exposure to maternal aflatoxin during fetal life as supported by the findings of Abdulrazzaq et al [22] who found a strong correlation (p <0.0001) between mothers' and cord blood levels of aflatoxin. Another possibility is that these children share the same type of foods with their mothers which might be the source of aflatoxin for both of them.…”
Section: Discussionsupporting
confidence: 78%
“…The aflatoxin -albumin adduct level of the infant at 16 weeks significantly negatively correlated (P, 0·05) with infant growth (52) . These studies are further supported by data in additional epidemiological studies (117,118) .…”
Section: Aflatoxin Biomarker Levels Are Associated With Growth Falteringsupporting
confidence: 73%
“…Other studies show associations between aflatoxins and stillbirths (Lamplugh et al 1988;Vries et al 1989), liver cirrhosis (Kuniholm et al 2008), jaundice in newborns (Abdulrazzaq et al 2004;Abulu et al 1998;Ahmed et al 1995;Sodeinde et al 1995) and immunosuppression (Jiang et al 2005;Turner et al 2003).…”
Section: Cgiar Agricultural Research On Food Safety and Aflatoxinsmentioning
confidence: 94%
“…Other studies in the Gambia and Kenya found significant association between aflatoxin exposure and wasting (Okoth and Ohingo 2004). Four studies (Abdulrazzaq et al 2002;Abdulrazzaq et al 2004;Abulu et al 1998;Turner et al 2007) reported a negative correlation between birth weight and aflatoxin levels; two studies found this relationship only when the sex of the infant was female (Jonsyn et al 1995a;Vries et al 1989).…”
Section: Cgiar Agricultural Research On Food Safety and Aflatoxinsmentioning
confidence: 95%